EFEKTIVITAS PROGRAM ESP DALAM MENINGKATKAN PEMAHAMAN GIZI KELUARGA PADA ANAK STUNTING DI PERCUT SEI TUAN - SULASTRI BR GINTING; Tedty Rohaya Tinambunan; Novrika Silalahi; Rizka Annisa (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2026)
Stunting remains a significant public health challenge in Deli Serdang Regency, often exacerbated by low health literacy and linguistic barriers in understanding global nutritional information. This study aims to evaluate the effectiveness of an English for Specific Purposes (ESP) program in improving nutritional understanding among families with stunted children in Percut Sei Tuan District. The ESP program was specifically designed to equip parents with the ability to understand functional nutritional terminology, food labels, and basic health instructions. This study employed a Pre-Experimental (One-Group Pretest-Posttest) design conducted with 22 respondents selected through purposive sampling. The intervention was carried out over five days, from January 19 to 23, 2026. Data were collected using structured questionnaires and analyzed using the paired sample t-test. The results indicated a statistically significant increase in the respondents nutritional understanding. The mean score rose from 54.1 at pre-test to 83.0 at post-test (p < 0.05). These findings prove that mastering technical nutritional terms through an ESP approach enhances parents self-efficacy in interpreting nutritional information and selecting healthy food. In conclusion, integrating functional language literacy into health interventions is an effective and innovative strategy to accelerate the reduction of stunting rates at the household level.